A brief review of natural convection in enclosures under localized heating with and without nanofluids - Öztop, Hakan Fehmi; Estelle, Patrice; Yan, Wei-Mon; Al-Salem, Khaled; Orfi, Jamel; Mahian, Omid (Pergamon-Elsevier Science Ltd, 2015)
In this work, natural convection heat transfer and fluid flow is reviewed in different types of enclosures with localized heating, considering the working fluid as a simple fluid or a nanofluid. Experimental findings are considered in addition to two and three dimensional numerical studies. The common objective of the reviewed work is to investigate the effects of type and location of local heat sources as well as the effects of the different configurations of cavities and boundary conditions on the enclosed fluid flow and heat transfer. Important correlations, concluded from these studies, are summarized. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Cavity; Heat generation; Porous; Localized heat source